Komunikasi Masyarakat Eks Lokalisasi Pasca Penutupan Dolly - Moefad, Agoes Moh. (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2015)
Social communication is the activity aimed for unifying social components, which have various and different behaviors. Communication is a reflection of the existence of community social life, so human can argues, empathizes and relates with the others. This study used a phenomenological approach so communication phenomena in ex-Dolly society Surabaya can be understood as an experience of self-awareness in daily activities. The society there basically produces experiences that later will be constructed into meaningful action in their social life. The findings of this study are expected to provide insight into the values of communication to the public in the context of socio-humanitarian.